Strategi Pengembangan Wana Wisata Sumber Biru Kabupaten Jombang untuk Meningkatkan Kunjungan Wisatawan Domestik - Farah Husniar; Muhafidhah Novie (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Tourism is defined as an activity that involves traveling to another place for the purpose of recreation or entertainment. A tourism development strategy is a series of plans and policies designed to improve and promote the tourism sector in a region. Jombang Regency, which is located in East Java, is one of the areas that has quite large potential in terms of the tourism sector. In this area there is a lot of abundant natural potential and can be seen from the many tourist attractions that have emerged from this region, but because of this competition between places tourism in this area is getting tighter. In facing intense competition in the tourism sector, it is necessary to choose the right strategy when maintaining, developing and improving a tourist attraction. From this, the author is interested in conducting research on the Sumber Biru Tourism Area which is located in the Wonosalam sub-district, which is located in Wonomerto Village, which aims to find out the supporting and inhibiting factors so that we can obtain information about the Development Strategy for the Sumber Biru Tourism Area to increase tourist visits. The method in this research uses qualitative research. The data collection method used in this research is primary data in the form of observations carried out at the Sumber Biru Jombang Tourism Village and interviews. Then secondary data by getting information from previous research